Making Work Pay in Madagascar : Employment, Growth, and Poverty Reduction - Hoftijzer, Margo (Washington, DC: World Bank, 2012)
There is little doubt that economic growth contributes significantly to poverty reduction; however, countries clearly differ in the degree to which income growth translates into reduced levels of poverty. Although cross-country estimates suggest that differences in the responsiveness of poverty to income growth account for a small fraction of overall differences in poverty changes across countries, from the point of view of an individual country these differences may have significant implications for poverty reduction, especially in the short term. The report is structured into eight chapters, beginning with this introduction. Chapter two describes the data and the main definitions used in this report. Chapter three provides the socioeconomic context of the study, with a particular emphasis on growth, poverty, and labor market characteristics. Chapter four takes a look at the linkages between macro and microeconomic data by reviewing the ways in which changes in aggregate and sectoral labor productivity translate into individual earnings as gathered from the household surveys. Chapter five also reviews the relationships between productivity and earnings by looking at the linkages between changes in aggregate and sectoral labor productivity data (macro) and changes in individual earnings as gathered from the household surveys (micro). Chapter six examines the origins and determining factors of household earnings and employment and assesses their impact on poverty and poverty reduction. Chapter seven analyzes the individual and household characteristics that are associated with having either 'good' jobs or 'bad' jobs and reviews the question of whether there may be barriers preventing the movement of workers from bad to good labor market segments. Finally, chapter eight describes the main conclusions of this report and provides suggestions for future work based on these conclusions.